Advanced Composites for Aerospace, Marine, and Land Applications - Sano, Tomoko; Srivatsan, T.S.; Peretti, Michael; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The papers in this volume cover a broad spectrum of topics that represent the truly diverse nature of the field of composite materials. This collection presents research and findings relevant to the latest advances in composites materials, specifically their use in aerospace, maritime, and even land applications. The editors have made every effort to bring together authors who put forth recent advances in their research while concurrently both elaborating on and thereby enhancing our prevailing understanding of the salient aspects related to the science, engineering, and far-reaching technological applications of composite materials.
Keywords: Mechanical engineering; Ceramic materials; Materials -- Analysis; Mechanical Engineering; Ceramics; Characterization and Analytical Technique